Avaliação do pontecial de produção de ovinos de corte em pastagens de Urochloa brizantha (syn. Brachiaria) no nordeste do Brasil - Joelma da Silva Souza (2020)
The objective of this study was to evaluate the productive potential, structural characteristics, nutritive value of Urochloa brizantha cultivars and sheep production. The treatments consisted of four cultivars: Marandu, Xaraés, BRS Piatã and BRS Paiaguás, evaluated in two seasons: wet season and dry season. Pastures were managed by an intermittent grazing method. Santa Inês sheep were used consisting of 24 females and 24 castrated males. There was no difference between cultivars and seasons evaluated during both the occupation and rest periods of 11.65 and 54.6 days, respectively. In the wet season, the Marandu cultivar presented a higher forage mass than the other cultivars (2,817.7 kg / ha of DM). The Xaraés cultivar stood out for its high percentage of leaf and leaf/stem ratio (68.7% and 4.28). The accumulation and rate of forage accumulation did not differ between cultivars and seasons (2327.57 kg / ha of DM and 40.44 kg / ha / day of DM). The season type did effect (P <0.05) the percentage of crude protein in the cultivars, with a higher content being observed in the wet season (9.09%). The type of cultivar also affected (P <0.05) the final weight of the sheep, the greatest gains were observed in the Marandu and Piatã cultivars. A relationship between cultivars and season type on individual live weight gain, live weight gain per hectare and stocking rate was noted. The best results were observed in animals on Marandu and Piatã cultivars (7.66 and 8.03 kg; 642.07 and 602.59 kg / ha; 21.04 and 20.25 AU / ha, respectively). Other factors such as management of the sheep’s behavior, grazing time, rumination, leisure and bit rate also influenced the productive of the sheep. Biometric measurements differ according to sex and cultivars (p <0.05). Body weight showed a high correlation (> 70%) with the perimeter of the barrel, height of the anterior, thoracic perimeter and croup width. The equations that best estimated the sheep's body weight were: CC2 index and chest circumference. The Santa Inês sheep male and female showed different biometric measures growth between cultivars during the growth phase. The cultivars Marandu, Xaraés Piatã and Paiaguás are productive; however, the cultivars Marandu and Piatã may be the most suitable for sheep production in regions with water restrictions given that they favored the best performance and body development of the sheep.